Sistem Pakar Berbasis Web untuk Membantu Diagnosa Penyakit Menular Seksual (Gonore, Sifilis, Chancroid, Herpes Simpleks, Kondiloma Akuminata) dengan metode certainty factor - Titania Dwi Andini; Pramanita Sutiawati (Jurnal Ilmiah Teknologi Informasi Asia, 2012)
Sexually Transmitted Infections mean illnesses that have a significant probability of transmission between humans by means of human sexual behavior, This illnesses have been growing rapidly in recent years which may have reached hundreds of them. Then, Artificial Intelligence is one of the solutions to diagnose the illnesses based on any symptoms felt. In this study the concept of forward chaining and certainty factor (CF) are used properly while a web-based system platform is preferred to diagnose Sexually Transmitted Infections (STI). This system is able to provide a diagnosis result of STI based on the symptoms felt by the patient, without having asked toward the Doctor. Furthermore, the results of this study are able to show that CF can be used as a way to cope with uncertainty in the case of STI diagnosis. Keywords: expert systems, certainty factor, sexually transmitted diseases